LITERATURE REVIEW: PENGGUNAAN KOMIK DIGITAL SEBAGAI MEDIA PEMBELAJARAN UNTUK MENINGKATKAN KEMANDIRIAN BELAJAR DAN BERPIKIR KRITIS - Sutomo, Sutomo; Kusmaryono, Imam (Jurnal Riset Madrasah Ibtidaiyah (JURMIA), 2025)
In the digital era digital era, the use of digital comics as a learning medium has shown significant potential in improving learning independence and learning outcomes. has shown significant potential in improving learning independence and critical thinking skills of students' critical thinking skills, especially at the elementary school level. This research aims to This study aims to review and analyze various literatures related to the the use of digital comics in educational contexts, in order to identify potential, benefits, and challenges of its application by analyzing 15 relevant articles. The method used is a narrative approach to review the existing literature, focusing on the impact of digital comics on the cognitive and affective aspects of students. on students' cognitive and affective aspects. The results of the analysis show that digital comics not only improve students' motivation and understanding, but also encourage active engagement in the learning process. also encourage active engagement in the learning process. Although there are challenges in their implementation, such as technology dependency and access gaps, recommendations for best practices in using digital comics in the classroom can help optimize their benefits. digital comics in the classroom can help optimize their benefits. This research is expected to contribute to the development of more innovative and effective more innovative and effective learning methods in schools.